Effect of styrene-butadiene-styrene addition on polystyrene/high-density polyethylene blends - TAŞDEMİR, MÜNİR (JOHN WILEY & SONS INC, 2002)
In order to prepare an ideal mixture, the physical and chemical properties of the constituent polymers must be known in detail. Thus, selection of the polymers that will constitute the mixture and a thorough study of the mixing methods and the economic factors become important. A rigid plastic is toughened by dispersing a small amount of rubbery material (generally 5-20%) in the rigid plastic matrix. Such a mixture of plastics is characterized by its impact resistance. Among thermoplastics toughened in this way are polystyrene (PS), poly(vinyl chloride), poly(methyl methacrylate), polypropylene, polycarbonate, and nylons, and recently thermoset resins such as epoxies, unsaturated polyester resins, and polyamids. In this study PS and high-density polyethylene polymers were mixed in various ratios. In order to increase the compatibility of the mixtures, 5, 7.5, and 10% SBS copolymer was also added. The mixing operation was conducted by using a twin-screw extruder. The morphology and the compatibility of the mixtures were examined by using SEM and DSC techniques. Furthermore, the elastic modulus, yield and tensile strengths, percent elongation, Izod impact resistance, hardness, and melt flow index values of the polymer alloys of various ratios were determined. (C) 2002 John Wiley Sons, Inc.
Keywords: copolymer; polystyrene; mixtures; extrusion; microstructure; HAAKE INTERNAL MIXER; BLOCK COPOLYMER; MORPHOLOGY; PS